2022
DOI: 10.1136/gutjnl-2021-326050
|View full text |Cite
|
Sign up to set email alerts
|

Blocking hepatocarcinogenesis by a cytochrome P450 family member with female-preferential expression

Abstract: ObjectsThe incidence of hepatocellular carcinoma (HCC) shows an obvious male dominance in rodents and humans. We aimed to identify the key autosomal liver-specific sex-related genes and investigate their roles in hepatocarcinogenesis.DesignTwo HCC cohorts (n=551) with available transcriptome and metabolome data were used. Class comparisons of omics data and ingenuity pathway analysis were performed to explore sex-related molecules and their associated functions. Functional assays were employed to investigate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Cyp7b1 attenuates NAFLD in mice at thermoneutrality (Evangelakos et al, 2021). In addition to BA synthesis, CYP39A1 inhibits the transcriptional activity of c-MYC via its C-terminal region (Ji et al, 2022). Cyp39a1 was highly gene-dosage-dependently down-regulated in both the male and female GR LHet and LKO AS mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyp7b1 attenuates NAFLD in mice at thermoneutrality (Evangelakos et al, 2021). In addition to BA synthesis, CYP39A1 inhibits the transcriptional activity of c-MYC via its C-terminal region (Ji et al, 2022). Cyp39a1 was highly gene-dosage-dependently down-regulated in both the male and female GR LHet and LKO AS mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results have shown no significant correlation between PWY-5913 and significantly different microbes, which indicated that this different pathway uncovered a whole-level difference. Meanwhile, CYP39A1 encoded a member of the cytochrome P450 superfamily of enzymes and played an important role in tumor progression ( Khenjanta et al, 2014 ; Ji et al, 2022 ) and neurodegenerative disorder ( Vishweswaraiah et al, 2022 ). CYP39A1 might affect a variety of microbes and finally show the difference in the PWY-5913 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cyp39a1 is involved in the alternative bile aid synthesis [ 56 ], which plays a critical role in removing cholesterol and inhibiting the sterol accumulation in the liver [ 57 ]. Moreover, clinical studies showed that patients with hepatocellular carcinomas (HCC) had lower liver Cyp39a1 expression [ 58 , 59 ]. We found that HFD downregulated the expression of Cyp39a1 ; however, the ablation of gut microbiota upregulated the expression of Cyp39a1 .…”
Section: Discussionmentioning
confidence: 99%